Lonesome Dove - Wincer, Simon; Duvall, Robert; Huston, Anjelica; Jones, Tommy Lee, 1946-; McMurtry, Larry (Santa Monica, CA : Genius Entertainment, 2008)
Epic western about two former Texas Rangers who leave the south Texas town of Lonesome Dove on a cattle drive to the ranch country of Montana.
Based on the book by Larry McMurtry.
Features: on location with director Simon Wincer, "Blueprints of a masterpiece : original sketches and concept drawings," "Remembering Lonesome Dove : vintage interviews with Tommy Lee Jones, Robert Duvall and the rest of the cast," Lonesome Dove montage, interview with Pulitzer Prize-winning author Larry McMurtry, the making of an epic.
Robert Duvall, Angelica Huston, Tommy Lee Jones, Danny Glover, Diane Lane.
Originally broadcast on television in 1989.
TV rating: Not rated.
DVDs, Dolby digital 5.1 surround.
Keywords: McMurtry, Larry -- Film and video adaptations; Cattle drives -- West (U.S.) -- Drama; Cowboys -- West (U.S.) -- Drama; Television mini-series.; Made-for-TV movies; Fiction films; Based on the book; Feature films; Western films